Rolled knitted scaffolds based on PLA‐pluronic copolymers for anterior cruciate ligament reinforcement: A step by step conception. Issue 4 (5th January 2016) - Pinese, Coline; Leroy, Adrien; Nottelet, Benjamin; Gagnieu, Christian; Coudane, Jean; Garric, Xavier
Abstract: The aim of this study was to prepare a new knitted scaffold from PLA‐Pluronic block copolymers for anterior cruciate ligament reconstruction. The impact of sterilization methods (beta‐ray and gamma‐ray sterilization) on copolymers was first evaluated in order to take into account the possible damages due to the sterilization process. Beta‐ray radiation did not significantly change mechanical properties in contrast to gamma‐ray sterilization. It was shown that ACL cells proliferate onto these copolymers, demonstrating their cytocompatibility. Thirdly, in order to study the influence of shaping on mechanical properties, several shapes were created with copolymers yarns: braids, ropes and linear or rolled knitted scaffolds. The rolled knitted scaffold presented interesting mechanical characteristics, similar to native anterior cruciate ligament (ACL) with a 67 MPa Young's Modulus and a stress at failure of 22.5 MPa. These findings suggest that this three dimensional rolled knitted scaffold meet the mechanical properties of ligament tissues and could be suitable as a scaffold for ligament reconstruction. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 735–743, 2017.